Proceedings of SPE Annual Technical Conference and Exhibition 2003
DOI: 10.2523/84354-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Cutting Structure Improves PDC Bit Performance in Hard Rock Drilling Environments

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractHard rock applications continue to pose serious challenges for PDC bits. Although improvements 1,2,3 have been achieved in these environments, PDC bit performance is highly inconsistent and leaves much to be desired.Operational costs in such environments, due to reduced footage and/or low penetration rates (ROP), are enormously high. This paper will evaluate the challenges of hard rock drilling. It will discuss the effects formation hardness has on drilling e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that the abrasive wear occurred caused by low DOC, while high DOC caused an impact wear (Van Quickelberghe et al, 2006). The wear occurs while the bit is rotating but not cutting (Mensa-Wilmot et al, 2003). This was confirmed by Gouda et al (2011) who stated that no torque leads to wear.…”
Section: Computational Model Of Pdc Bit Lifementioning
confidence: 79%
“…It has been reported that the abrasive wear occurred caused by low DOC, while high DOC caused an impact wear (Van Quickelberghe et al, 2006). The wear occurs while the bit is rotating but not cutting (Mensa-Wilmot et al, 2003). This was confirmed by Gouda et al (2011) who stated that no torque leads to wear.…”
Section: Computational Model Of Pdc Bit Lifementioning
confidence: 79%